Regendering of dynamic managerial capabilities in the context of binary perspectives on gender diversity. Issue 1 (10th January 2020) - Kamasak, Rifat; Ozbilgin, Mustafa; Kucukaltan, Berk; Yavuz, Meltem
Abstract : Purpose: The interplay between gender and dynamic managerial capabilities is not well studied in the extant literature. This paper aims to explore how dynamic managerial capabilities, as prized qualities in the job market, are framed in gendered ways and how the gendering process disadvantages female and male workers for different reasons and harms the organisations, which use the managerial capabilities approach without proofing it for gender biases. Design/methodology/approach: An extensive literature review was conducted and a framework that offers a new gender perspective was offered. Findings: A number of ways dynamic managerial capabilities may be proofed for gender biases and how a gender-balanced framing of dynamic managerial capabilities may be achieved are identified. Originality/value: This paper contributes to the development of a new gender perspective, which is called regendering of dynamic managerial capabilities, which frees the concept from its binary frames of gender, assumptions of gender neutrality, with a view to capture gender diversity in a way which is closer to its nature in theory and practice of dynamic managerial capabilities.